2021
DOI: 10.3390/biom11040547
|View full text |Cite
|
Sign up to set email alerts
|

EPLIN Expression in Gastric Cancer and Impact on Prognosis and Chemoresistance

Abstract: Epithelial protein lost in neoplasm (EPLIN) has been implicated as a suppressor of cancer progression. The current study explored EPLIN expression in clinical gastric cancer and its association with chemotherapy resistance. EPLIN transcript expression, in conjunction with patient clinicopathological information and responsiveness to neoadjuvant chemotherapy (NAC), was explored in two gastric cancer cohorts collected from the Beijing Cancer Hospital. Kaplan-Meier survival analysis was undertaken to explore EPLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…EPLIN has been implicated to play a role in drug resistance in prostate cancer [ 12 ] and gastric cancer [ 29 ]. Likewise, HSP60 has also been implicated in mediating drug resistance in ovarian cancer [ 30 ] and colorectal cancer [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EPLIN has been implicated to play a role in drug resistance in prostate cancer [ 12 ] and gastric cancer [ 29 ]. Likewise, HSP60 has also been implicated in mediating drug resistance in ovarian cancer [ 30 ] and colorectal cancer [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…qPCR was carried out to assess transcript expression of genes of interest. Amplifilour Uniprimer TM Universal system (Intergen company, New York, USA) was utilised for qPCR [ 29 ]. In brief, each reaction was made up with 5 μL precision FAST2x qPCR Master Mix (PrimerDesign, Southampton, UK), 0.3 μL forward primers (EPLIN: AAGCAAAAATGAAAACGAAG; GAPDH: AAGGTCATCCATGACAACTT; Her1: GACCTCCATGCCTTTGAGAA; Her2: CCTCCTCGCCCTCTTG; Her3: CCCCACACCAAGTATCAGTA; Her4: CTGCTGAGTTTTCAAGGATG; HSP60: TGTAGACCTTTTAGCCGATG), 0.3 μL reverse primer with z sequence whose concentration was 1/10 of forward primer (EPLIN: ACTGAACCTGACCGTACAGACACCCACCTTAGCAATAG; GAPDH: ACTGAACCTGACCGTACAGCCATCCACAGTCTTCTG; Her1: ACTGAACCTGACCGTACAGCACAAATTTTTGTTTCCTGA; Her2: ACTGAACCTGACCGTACACATGTCCAGGTGGGTCT; Her3: ACTGAACCTGACCGTACAACACAGGATGTTTGATCCAC; Her4: ACTGAACCTGACCGTACAAACTTGCTGTCATTTGGACT; HSP60: ACTGAACCTGACCGTACAACAGTCACACCATCTTTTGT) (Sigma-Aldrich Co, Poole, Dorset, UK), 0.3 μL uniprimer and 4.1 μL cDNA samples.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, important work by Zhang et al revealed that a lower level of EPLIN is related to poor prognosis and is implicated in chemo drug resistance in prostate cancer [9]. The initial finding that EPLIN may have a role to play in drug resistance has recently been supported by a more clinically oriented finding in gastric cancer [50], in that higher expression was generally seen in cancers that responded to neoadjuvant chemotherapy (NAC) compared to those that did not, though this was not significant. Furthermore, a greater overall survival distribution in patients displaying higher expression of EPLIN was observed, based on responsiveness to NAC.…”
Section: The Clinical Aspects Of Eplin In Human Cancersmentioning
confidence: 99%
“…EPLIN has been implicated in playing a role in the development and progression of solid cancers. Keeping in line with the findings that EPLIN contributes to maintaining the epithelial cytoskeleton, regulating metastatic progression and cell cytokinesis, there has been strong scientific focus on EPLIN and its implications in multiple types of cancer including oral cancer [1,4], breast cancer [4,44], prostate cancer [2,9], squamous cell carcinoma of head and neck (SCCHN) [9], lung cancer [45], oesophageal cancer [46], ovarian cancer [47], colorectal cancer (CRC) [9,16,18,48,49] and most recently gastric cancer [50]. EPLIN has also been revealed to be associated with multiple cellular functions such as cell motility, migration, invasion and proliferation, in a number of different cancer cell lines [2,9,25,[44][45][46][47]51].…”
Section: The Clinical Aspects Of Eplin In Human Cancersmentioning
confidence: 99%
“…For instance, P53 binds to the response elements in the LIMA1 gene and induces LIMA1 expression, causing the suppression of tumour invasion [ 6 ]. Higher LIMA1 expression increased patient responsiveness to neoadjuvant chemotherapy (NAC), which greatly improved patient survival [ 7 ]. Apart from its tumour-suppressing function, LIMA1 also exerts effects on the pluripotency control of membrane dynamics and cellular metabolism [ 8 ].…”
Section: Introductionmentioning
confidence: 99%